First Episode Mania at the Age of 78 Years: A Case Report - Dhonju, G; Singh, PM; Joshi, N (Journal of Psychiatrists' Association of Nepal, 2014)
Late onset psychiatric disorders generate interest due to frequent association with some organic, neurological or metabolic etiology. Primary psychiatric illness with an onset in late life is rare. Late onset mania has not been frequently encountered and hence we are reporting a case of a 78 year old male diagnosed with first episode mania with psychotic symptoms. DOI: http://dx.doi.org/10.3126/jpan.v3i1.11352 J Psychiatrists’ Association of Nepal Vol .3, No.1, 2014: 43-44